Discrete Aurora on Mars: Insights Into Their Distribution and Activity From MAVEN/IUVS Observations. Issue 10 (8th October 2021) - Schneider, N. M.; Milby, Z.; Jain, S. K.; Gérard, J.‐C.; Soret, L.; Brain, D. A.; Weber, T.; Girazian, Z.; McFadden, J.; Deighan, J.; Jakosky, B. M.
Abstract: Mars Atmosphere and Volatile Evolution (MAVEN)'s Imaging Ultraviolet Spectrograph has identified 278 occurrences of discrete aurora events on Mars, which are patchy, sporadic ultraviolet emissions emanating from the upper atmosphere. We confirm prior results finding that emissions are highly correlated with crustal magnetic fields results, with the brightest and most frequent occurrences located around strong crustal fields in the southern hemisphere. The six‐year data set shows that events can also occur globally, in regions of weak or absent crustal fields. We find that events occur primarily in evening hours, especially during favorable orientations of the interplanetary magnetic field. Under these conditions, auroral events probably occur nightly and last for hours. Optical counterparts to these UV emissions would probably be detectable with present‐day instrumentation, and would be visible to future astronauts. Plain Language Summary: Mars has an unusual magnetic field: it lacks a global field but retains the vestiges of an ancient field locked in regions of the crust. These fields are sufficient to focus charged particle precipitation into the atmosphere and cause aurora. The Mars Atmosphere and Volatile Evolution (MAVEN) spacecraft carries an ultraviolet instrument capable of mapping aurora emissions and correlating them with conditions that favor aurora. We have detected hundreds of auroral events allowing the first statistical study of their behavior. We find that events occur primarily in evening hours, especially during favorable orientations of the interplanetary magnetic field. Under these conditions, auroral events probably occur nightly and last for hours. Astronauts, whenever they reach Mars, would have a good chance to see this natural wonder from above or below. Key Points: Mars Atmosphere and Volatile Evolution (MAVEN)/Imaging UltraViolet Spectrograph (IUVS) has detected hundreds of transient, patchy auroral emission events at Mars, mostly near strong crustal magnetic fields Events are triggered in evening hours during favorable orientations of the interplanetary magnetic field, and may last for hours Visible counterparts to the ultraviolet emissions could potentially be imaged by spacecraft and eventually seen by astronauts